Images of Florida in the Haitian Novel of Exile - Joubert Satyre (Journal of Transnational American Studies, 2017)
This article examines how Florida is depicted in Passages (1991) by Émile Ollivier and in Cette grenade dans la main du jeune nègre est-elle une arme ou un fruit? (2002) by Dany Laferrière. The theoretical framework for this examination is “imagology,” which Jean-Marc Mourra describes as the study of the literary representation of Otherness. According to Mourra, this representation can be utopian or ideological. In the first category, Otherness is portrayed in a positive way, while in the second category, the portrayal is negative. The representation of Florida in the above novels swings between the two.